2005
DOI: 10.1016/j.seizure.2005.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Seizure freedom with different therapeutic regimens in intellectually disabled epileptic patients

Abstract: In a majority of intellectually disabled patients with epilepsy (including those who became seizure free since 1992), complete seizure control has been achieved by monotherapy or duotherapy with classic AEDs. Of the new AEDs LTG in combination with VPA appears to be an important innovation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…This however reflects advice given in the NICE guidelines and has been previously shown to be of significance. [9][10][11] Increasing the amount of time of each appointment allowed us to explore nursing and psychosocial issues.…”
Section: Discussionmentioning
confidence: 99%
“…This however reflects advice given in the NICE guidelines and has been previously shown to be of significance. [9][10][11] Increasing the amount of time of each appointment allowed us to explore nursing and psychosocial issues.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of epilepsy in PWID, a Treatment of epilepsy Huber and Seidel 493 number of studies on different new AEDs have been published, but the relative value of the new compounds compared with the classic AEDs has remained unclear. A recent study [8 ] stressed the importance of the classic drugs.…”
Section: Pharmacological Therapy In Generalmentioning
confidence: 99%
“…In a large retrospective survey [8 ] on residential patients with epilepsy and intellectual disability of different degrees, the authors investigated the therapy regimens of patients who became seizure free. Two hundred and forty of the 675 patients (35.6%) included were seizure free.…”
Section: Pharmacological Therapy In Generalmentioning
confidence: 99%
“…In their study with 214 intellectually disabled patients Kelly et al found that antiepileptic drugs introduction and change resulted in seizure freedom for more than 40% of the subjects enclosed [3]. Of 240 seizure free patients with ID studied by Huber et al, 50.8% were on monotherapy, 38% were treated with two, and the rest received more than two anticonvulsants OPEN    ACCESS [5]. Except from valproic acid (VPA) in combination with lamotrigine (LTG) there was no comedication with newer anticonvulsants in most of the cases in this study.…”
Section: Introductionmentioning
confidence: 99%